Peningkatan Pengetahuan Masyarakat tentang Metode Pengelolaan dan Pembuatan Penangkap Sampah Mikroplastik - Nawan Prianto; Karbito; S.Rendra Utama R (CV. CENDIKIA JENIUS INDONESIA, 2025)
Marine pollution caused by plastic waste, particularly microplastics, poses a serious threat to the environment and seafood safety. Indonesia is the second-largest contributor of plastic waste in the oceans globally. The coastal area of Sukaraja in Bandar Lampung is one of the affected regions, where communities still have limited awareness of the dangers of microplastics. This activity aimed to increase public knowledge regarding the management and construction of microplastic waste traps. The implementation method was carried out through the Community Partnership Program in three stages: planning, implementation, and education, which included lectures, discussions, and hands-on practice in building waste traps. The results showed that community understanding of waste management improved, and waste traps were successfully constructed using PVC pipes and cement molds. However, due to the large variety and volume of waste, microplastic-specific traps proved ineffective and were redirected to general waste traps. Ongoing support is needed in the form of dedicated waste management personnel, adequate collection facilities, and coordination among related agencies. This activity successfully raised community awareness and capacity in addressing waste issues in coastal areas.